THE INFLUENCE OF PROMOTION AND STORE ATMOSPHERE ON IMPULSE PURCHASES OF VISITORS TO KEBUMEN NEW DEPARTMENT STORES - Lutfiatin, Meiliana; Rahardjo, Budi (Manager : Jurnal Ilmu Manajemen, 2023)
The purpose of this research is to determine the effect of promotion and store atmosphere as independent variables on the impulsive buying of visitors Jadi Baru Kebumen Department Store. In taking the sample, non-probability sampling method was used with purposive sampling technique. Data was obtained by distributing questionnaires to prospective respondents through various social media. Based on the results of the questionnaire, data from 100 respondents was obtained which was then processed using SPSS version 25 with multiple linear regression methods, namely there was a finding that the promotion variable had a negative influence on impulsive buying. Meanwhile, the store atmosphere variable has a positive influence on the impulsive buying of Jadi Baru Kebumen Departement Store visitors. The results of this research can have implications for managers to be able to evaluate the promotional strategies they apply and pay attention to and improve the store atmosphere at Jadi Baru Kebumen Departement Store